Edukasi Pendidikan Karakter â€œCinta Lingkunganâ€ Melalui Pemanfaatan Gelas Plastik Sebagai Media Penanaman Bawang Merah - Dheny Arina Hartawaty; Ertha Martha Intani; Dewi Masithoh (Lamahu)
The character education of "love of environment" can be instilled early in elementary school children. One of the efforts is through a plastic cup waste management program as a pot for planting shallots. This educational program was implemented at Madrasah Ibtidaiyah Al Hadi II, Bangunjiwo, Bantul in December 2023 using the participatory method. This activity aims to educate primary school students to have the character of "love of environment" by using plastic cup waste as a medium for planting shallots. The series of program implementation activities consisted of 3 stages, specifically material counseling, practice of planting shallots in plastic cups, and evaluation of the understanding of the educational program provided. Through this service activity, a positive impact was achieved for the students by providing valuable experience in the form of: (1) most of the participants seemed to have an increased awareness of the importance of preserving the environment and could be applied in students' daily lives; (2) 90% of the participants actively participated in the program and there were results in the formation of a positive character "love for the environment" among elementary school students; (3) there was an increase in students' understanding in the use of used goods as planting media both in the school environment and the surrounding environment